Pengaruh E-Word Of Mouth Dan E-Trust Terhadap E-Purchase Decision Mahasiswa Universitas Negeri Padang Pada Marketplace Lazada - Azizah Pratika Sari; Rose Rahmidani (Jurnal Ecogen, 2019)
This study aims to know 1) the influence E-Word of Mouth to E-Trust toward E-Purchase Decision Universitas Negeri Padang students on marketplace Lazada, 2) the influence E-Word of Mouth toward E-Purchase Decision Universitas Negeri Padang students on marketplace Lazada, 3) the influence E-Trust toward E-Purchase Decision Universitas Negeri Padang students on marketplace Lazada. The type of study is causal research. The population in this study are Universitas Negeri Padang students who once using marketplace Lazada. The sampling techniques using non probability sampling with purposive sampling method and sample size of 100 respondens by using the formula of Cochran’s. The data analysis technique used is the analysis of the path (path analysis) using SPSS version 21. By using path analysis, the resultsof this study  showed that: (1) E-Word of Mouth have effect on E-Trust toward E-Purchase Decision Universitas Negeri Padang students on marketplace Lazada, (2) E-Word of Mouth affects E-Purchase Decision Universitas Negeri Padang students on marketplace Lazada, (3) E-Trust affects E-Purchase Decision Universitas Negeri Padang students on marketplace LazadaKeyword: E-Word of Mouth, E-Trust, E-Purchase decision